(untitled) (The Conference Hub, 2025)
Currently, the reforms being implemented in our country are fundamentally changing the content of social relations. In this context, the need to raise the younger generation with a spirit of diligence is steadily increasing. In particular, special attention is being paid to adopting the experience of the most advanced countries in the world in this field. One of the pressing and increasingly important issues of global interest is guiding young people toward professions. It has been shown that selecting professions for youth based on their interests, talents, and abilities is the most appropriate approach [2].